(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Interviews are one of the popular data collection methods used in qualitative approaches. Interviews can expose the researcher to a large and unlimited amount of data. Through interviews, some new things may be discovered based on the opinions given. Effective interviews are able to provide sufficient data for a study. The interview session takes place over a certain period of time with certain conditions set. The results of the interviews will be transcribed and will be analyzed. However, before all the procedures are carried out, the basic thing that needs to be prepared is the interview protocol. This article describes the formation of an interview protocol based on school leadership issues on workload and job satisfaction of special education teachers.